Vidéki civilek - vidéki forrásteremtési lehetőségek - Szabados György; Kulcsár Gergely (2017)
The structure and activity of locally registered civil organizations has an impact of the life of every settlement, and in most cases it is strongly associated with their capabilities to raise funds and other kind of grants. In rural settlements, among the locally registered civil organizations by all means could be justified to make a difference on the basis of an essential aspect, that how extro- or introverted are these organizations with regard to their resources, and because of certain aspects it is closely related with the local political elites activity. In our empirical research we seek for the answer through the example of a small rural town, that what kind of fund raising opportunities can the locally registered civil organizations establish, and are these civil organizations in the state of emergency or they „grow lazy” because of the uncertain or granted subsidies provided to them.